Parent-Child Communication About Marriage and the Displacement of Marital Myths - (:unkn) unknown (My University, 2013)
Marriage and divorce are common in the U.S. today, and the question of "why is the divorce rate so high?" lingers in popular culture. The purpose of this study is to examine the need for parent-child communication about marriage to determine if it can help to dispel marital myths that abound in U.S. society. This study takes a qualitative approach to the communication between parents and their children about the topic of marriage. Three research questions are asked regarding what messages were transmitted between parents and their (now adult) children about marriage, how accurate the children perceive these messages to be, and whether these messages have displaced or reinforced existing marital myths for these individuals. An inductive analysis revealed that several themes and sub-themes of messages were transmitted from parent to child about what marriage is, generally these messages were perceived to be accurate by the children, and largely, these messages appear to displace marital myth. Implications and limitations of this study, as well as future avenues for research on this topic, are discussed.
Keywords: Marital Myths; Parent-Child Communication